Numerical methods using MATLAB / George Lindfield, John Penny. - Lindfield, G. R. (George R.); Penny, J. E. T. (John E. T.) (Academic Press, 2018)
'Numerical Methods using MATLAB' is an extensive reference offering hundreds of useful and important numerical algorithms that can be implemented into MATLAB for a graphical interpretation to help researchers analyse a particular outcome.